2012
DOI: 10.1103/physrevb.85.115309
|View full text |Cite
|
Sign up to set email alerts
|

Polaron master equation theory of the quantum-dot Mollow triplet in a semiconductor cavity-QED system

Abstract: We present a comprehensive theoretical study of the resonance fluorescence spectra of an excitondriven quantum dot (QD) placed inside a high-Q semiconductor cavity and interacting with an acoustic phonon bath. We derive a quantum master equation (ME) in the polaron frame which includes exciton-phonon and exciton-cavity coupling to all orders. This work details and extends the theory used in a recent issue of Physical Review Letters (C. Roy and S. Hughes 2011: Phys. Rev. Lett. 106 247403) to describe the QD Mol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
106
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 65 publications
(109 reference statements)
6
106
2
Order By: Relevance
“…Note that while we do not include detailed cavity effects here, which give rise to qualitatively different behaviour in Refs. [30,31], our results demonstrate that for a QD TLS at least, an increase in sideband splitting off-resonance does not necessarily imply an associated phonon-induced increase in sideband width.Summary.-We have shown that the balance of coherent to incoherent emission from a driven TLS can be fundamentally altered by environmental interactions, leading to a nonstandard regime of resonance fluorescence attainable in solid-state emitters. In the context of driven QDs, enhanced coherent scattering can occur with increasing driving strength, due to thermalisation in the QD steady-state with respect to the phonon bath.…”
mentioning
confidence: 67%
“…Note that while we do not include detailed cavity effects here, which give rise to qualitatively different behaviour in Refs. [30,31], our results demonstrate that for a QD TLS at least, an increase in sideband splitting off-resonance does not necessarily imply an associated phonon-induced increase in sideband width.Summary.-We have shown that the balance of coherent to incoherent emission from a driven TLS can be fundamentally altered by environmental interactions, leading to a nonstandard regime of resonance fluorescence attainable in solid-state emitters. In the context of driven QDs, enhanced coherent scattering can occur with increasing driving strength, due to thermalisation in the QD steady-state with respect to the phonon bath.…”
mentioning
confidence: 67%
“…Though the damping of excitonic Rabi rotations (in the QD population) has been measured at various temperatures under pulsed excitation [14,15,17], the direct observation of temperature dependence in the field correlation properties and resonance fluorescence (RF) emission spectra of a single QD has not been reported. This is arguably the most relevant scenario for photonic applications, since it is crucial to understanding the competing roles played by the electromagnetic and solid-state environments in determining the QD optical emission characteristics and coherence [26][27][28][29].…”
mentioning
confidence: 99%
“…To account for these processes, we PRL [23,[26][27][28], which allows us to derive an explicit expression for the emission spectrum of the QD in terms of experimental parameters and microscopic constants characterizing the QD-phonon coupling. We model the excitonic degree of freedom of the QD as a two-level-system, and couple it to two harmonic oscillator baths, which represent both the electromagnetic field into which light is emitted, and the phonon environment present in the substrate.…”
mentioning
confidence: 99%
“…Most often, these methods fully account for the dotlight coupling but treat the exciton-phonon interaction within further approximations. Examples of such approaches are the time-convolutionless approach [116,120,121], the correlation expansion [122,123,124,125,126], different types of master equations [116,53,64,127,88,128,93] or time-dependent perturbation theory [129,125]. For the Hamiltonian dynamics within the model established by Eqs.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…In the case of strong light-matter coupling there is a strong interplay between exciton-phonon and light-matter interaction, which for example can be seen in the line-width broadening in the Mollow-Triplet [180,102]. The combined exciton-photon and exciton-phonon interaction in the strong coupling regime has been subject to many theoretical works [181,58,87,90,95,88,89,128,182,91]. A detailed discussion of the phenomena related to the interplay between these coupling mechanisms is beyond the scope of this review.…”
Section: Rabi Rotationsmentioning
confidence: 99%